2022
DOI: 10.3390/ijerph192013171
|View full text |Cite
|
Sign up to set email alerts
|

Levels, Distribution and Health Risk Assessment of Organochlorine Pesticides in Agricultural Soils from the Pearl River Delta of China

Abstract: To reveal the pollution status of agricultural soils along with rapid urbanization and economic growth, a large regional survey of organochlorine pesticides (OCPs) in agricultural soils was conducted in the Pearl River Delta (PRD) of China. The results showed that the total residues of 23 OCPs were in the range of ND-946 ng/g dry weight. OCP residues showed distinct spatial distribution characteristics within the PRD. OCPs were mainly found in areas with high agricultural production and industrial activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…Moreover, degradation of PAHs becomes enhanced under high temperature and strong sunlight during summer. In the PRD, the erosion of soil by rain will accelerate the migration and transformation of PAHs in soil [ 24 ], resulting in a high degree of soil weathering and leaching and increased soil microbial activity, thus accelerating the degradation of PAHs. However, in this study we did not investigate seasons as an influencing factor, which will be investigated in the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, degradation of PAHs becomes enhanced under high temperature and strong sunlight during summer. In the PRD, the erosion of soil by rain will accelerate the migration and transformation of PAHs in soil [ 24 ], resulting in a high degree of soil weathering and leaching and increased soil microbial activity, thus accelerating the degradation of PAHs. However, in this study we did not investigate seasons as an influencing factor, which will be investigated in the future.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of molecular weight, their volatility gradually decreases, and their existing form gradually changes from gaseous to granular state. Low molecular weight PAHs are easy to be volatilized and photolysis to atmospheric environment, while high molecular weight PAHs with higher K ow tend to be distributed on soil particles [ 24 ]. It also explains why PAHs are enriched at the bottom of the soil.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Tang et al (2020) found high DDT concentrations (average of 4.03 ng/g) in sediments of a particular region of the Pearl River Estuary (i.e., Humen outlet), representing a medium ecological risk. Moreover, a quite recent publication from Yao et al (2022) detected high concentrations of total OCPs (average of 65.5 ng/g) in soils of the PRD. Among them, DDTs accounted for the largest share with an average concentration of 34.2 ng/g followed by HCHs (4.52 ng/g).…”
Section: Highlightsmentioning
confidence: 95%
“…Currently, HCHs residues can still be detected in soil in many areas of China. Yao et al found agricultural soil contaminated with OCPs, such as HCH, in the Pearl River Delta [4]. Liu et al found residues of HCHs and DDT in the sediment analysis of Xinhe and coastal wetlands in Yongding, with ecological risk assessments showing high risks [5].…”
Section: Introductionmentioning
confidence: 99%